Letter - Ilkeston Trades Council & Labour Party, 10 May 1926 (Ilkeston)
1926-05-10 "Letter - Ilkeston Trades Council & Labour Party, 10 May 1926" [g0362001.jpg], 10 May 1926, Ilkeston Trades Council & Labour Party Local Organisation